Targeted superparamagnetic nanoparticles coated with 2-deoxy-d-gloucose and doxorubicin more sensitize breast cancer cells to ionizing radiation. (June 2017) - Pirayesh Islamian, Jalil; Hatamian, Milad; Aval, Negar Abbasi; Rashidi, Mohammad Reza; Mesbahi, Asghar; Mohammadzadeh, Mohammad; Asghari Jafarabadi, Mohammad
Abstract: Introduction: Nanoparticles are promising as a new approach to enhance chemo- radiotherapy efficiency in breast cancer mainly via targeted therapy. Materials & methods: SKBR3 and T47D breast cancer cells were treated with superparamagnetic mesoporous hydroxyapatite nanocomposites (SPmHANs)conjugated with 1 μM doxorubicin and 0.5 mM 2-Deoxy-d -Glucose and irradiated with 1 and 2 Gy gamma rays in vitro. The treatment toxicity and also the apoptosis/necrosis ratio were measured by MTT assay and also ELISA cell death detection PLUS, respectively. Results: The decreased cell viability with the combined treatment, with determined 42% loading efficiency for 200 ppm 2DG and 93% for5ppm doxorubicin on SPmHANs in PH about 7.4 and 5.5, were calculated to 60.9% and 68% compared to radiotherapy alone inT47D and SKBR3 cells (both with p < 0.05), respectively. Conclusion: Breast cancer cure may boost from The combined targeted nanoparticle treatment with doxorubicin and 2-Deoxy-d -Glucose may boost breast cancer radiotherapy by improved chemodrug localization, increased cytotoxicity in tumor cells and decreased single modality treatment doses. Graphical abstract: The authors have examined the effects of combination of 2-deoxy-d-Glucose and Doxorubicin with superparamagnetic nanoparticles to enhancing the radiosensitivity of SKBR3 and T47D breast cancer cell lines. Highlights: New approach to enhance chemo- radiotherapy efficiency in breast cancer. Targeted drug delivery increases cytotoxicity in tumor cells and decreases the conventional therapy side effects. Combined targeted nanoparticle treatment with doxorubicin and 2-Deoxy-d-Glucose. A combination of 2DG, DOX and HA nanoparticles significantly reduces cancer cell viability.